The Impact of the Mediating Role of Green Organizational Culture on the Relation between Human Resources Green Competencies and Organizational Environmental Performance in Major Palestinian Governmental Hospitals in the Gaza Strip - AL-Ross, Sami; Abu Mahadi, Fatima (The Arab Journal of Administration, 2021)
This study aims at shedding light on the reality of human resource green competencies in Palestinian government hospitals in the Gaza Strip, clarifying the role of those competencies in improving organizational environmental performance. Furthermore, it clarifies the impact of green organizational culture on the relation between human resource green competencies and organizational environmental performance. The descriptive analytical approach was adopted. In addition, a questionnaire was designed to collect data from employees who work at nursing and administrative fields in government hospitals using two-stage cluster sample. Major conclusions indicated that the HR green competencies are weak among employees in the sampled hospitals. Moreover, there is a clear weakness in organizational environmental performance. In addition to weak green organizational culture. Eventually, it is recommended to design and initiate a clear environmental strategy and objectives. Furthermore, promote efforts to disseminate and encourage green culture, values, and beliefs among employees. Moreover, there is a need to develop and adopt practical and applicable green HRM functions. Also, educate and train employees to develop employees’ green competencies. In addition, to increase employees’ involvement and participation in green activities and solve environmental issues.